Evaluation of Latency, Range, and Path Redundancy in Multihop Communication Using the NRF24L01 Module - Dian Neipa Purnamasari; Adi Kurniawan Saputro; Moch. Roziqul Barqi; Puteri Nurul Ma’rifah; Achmad Ubaidillah Ms; Muttaqin Hardiwansyah (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
This research focuses on evaluating the performance of NRF24L01 module-based multihop wireless communication networks, specifically on latency, range, and path redundancy resilience. The network was designed with 8 nodes (1 sender and 7 router/receiver nodes) for data transmission. Response time (latency) is explicitly measured using synchronized timestamps from a Real Time Clock (RTC) DS3231 across all nodes. This performance-oriented study involved three main scenarios: 1) Line of Sight (LoS) to measure maximum range and baseline latency, 2) Non-Line of Sight (NLoS) to test the impact of physical obstacles, and 3) Automatic Routing and Path Redundancy testing to evaluate the failover capability. In the LoS scenario, effective communication reached 310 meters with an average latency of 1,046 ms. Conversely, in the NLoS scenario, communication remained effective up to 33 meters with an average latency of 763 ms. The path redundancy analysis demonstrates that the system successfully performed a failover when an intermediate node was shut down, though it caused a net latency increase of more than 800 ms on the alternative path. These results confirm that NRF24L01 can provide reliable multihop connectivity suitable for long-distance monitoring applications.